SPARKOL VIDEOSCRIBE SEBAGAI MEDIA PEMBELAJARAN - Munawarah, Rofiqah Al (Inspiratif Pendidikan, 2019)
Learning media are aids in the learning process or communication and interaction tools between teachers and students which initially focused on visuals and audio, then develops with the use of computer technology in them whose purpose remains to achieve learning objectives. Scribe sparkol video is a white background software that contains narration and is usually used to design an animation program which is then developed into one of the learning media that can be used to be more attractive to students, their use is very fast and easy. There are several advantages and disadvantages of using sparkol video scribe as a learning medium, so it would be very wise if in our use we use mature thought. In addition to the enormous benefits for students because they are able to increase their enthusiasm for learning by using combined technology (audio visual and computer), it cannot be ruled out that using this media requires complete equipment and can use relatively expensive costs when compared to using print media only.